Analisis Teknikal Sebagai Dasar dalam Pengambilan Keputusan dalam Trading Saham - Ramadhani, Fitri; Handayani, Putri; Sari, Rindi Elma; Rizal, Seliana (CV. Kalimasada Group, 2023)
Stock trading is the practice or activity of buying and selling stocks by utilizing price fluctuations every day. The purpose of this research is to see how technical analysis becomes the basis for making stock trading decisions. This research uses a qualitative method. The literature study used is a literature review, where all sources are taken from journals that have the same discussion as the research and then re-analyzed. The research population is all journals that have the same theme as the research, the sample is journals uploaded in the last 10 years on google schoolar. The results of this study are based on previous research that technical analysis is the basis for making stock trading decisions. This is because technical analysis provides investors with information that helps them understand how to buy and sell stocks to maximize profits so that when individuals trade stocks, they will get accurate information regarding stock market trends